Filozofia, humanistyka i nauki społeczne – wezwanie do ofensywy - Lekka-Kowalik, Agnieszka (Człowiek i Społeczeństwo, 2015)
The paper aims at justifying a call to go on the offensive in order to assure for philosophy, the humanities and social sciences a proper place in science as a whole. Against the background of the contemporary social context (transdisciplinary research, seeing science as a source of risks, rejection of a liner model of getting social benefits from basic sciences, recognizing stakeholders’ participation in research) the Author shows that any research project on life problems cannot be executed by natural or technical sciences alone, but it must engage philosophy, the humanities and social sciences. The same is true of applications of accepted solutions. The conclusion is that cooperation between natural, technical and social sciences, philosophy and the humanities is necessary in doing research and using its achievements. It is also required in education, if scientists and citizens are to act as stakeholders in democratic processes of shaping techno-scientific progress.